Cladopus yangjiangensis (Podostemaceae), a new species from Guangdong, South China, redefining the phylogenetic relationships within Cladopus - Miao Zhang; Xiu-Ting Liu; Min Tian; Zhang-Xue Chen; Ying-Lin Huang; Guo-Di Chen; Bing-Hua Chen (PhytoKeys)
This paper introduces Cladopus yangjiangensis, a newly identified species that enriches our understanding of the diversity of the Podostemaceae in East Asia. Distinctive in its morphological traits, this species is characterized by the region’s longest flowering shoots and exhibits a high number of elongated leaves per cluster, along with relatively slender roots. Phylogenetic analyses using Maximum Likelihood and Bayesian Inference methods on plastome and matK sequences confirm C. yangjiangensis as a distinct species. It forms a clade with C. fukienensis, its closest relative, together branching off from C. austrosinensis. The plastome of C. yangjiangensis is 132,818 bp in length, comprising two inverted repeat regions of 20,881 bp, which are separated by large and small single-copy regions of 78,713 and 12,343 bp, respectively. Genetic analysis reveals the extensive loss of the ycf1 and ycf2 genes in the chloroplast genome, a trait common to the Podostemaceae, suggesting adaptations to environmental conditions or gene transfers to nuclear or mitochondrial genomes. This study improves the clarity of phylogenetic relationships in previous studies and underscores the importance of continued taxonomic and phylogenetic research.